MODERN METHODS OF TEACHING FOREIGN LANGUAGES - Pulatova Moxigulxon Ilxomjon qizi; Egamberdiyeva Irodaxon (TADQIQOTLAR, 2025)
Annotation: This article discusses how to effectively conduct the process of teaching foreign languages, particularly in preschool and primary education, using modern technologies and engaging, simple methods that are suitable for children. It also highlights the methodological tools currently applied in our country to improve the quality of education.